Microbial Nitrogen Cycling Becomes Conservative and Resilient to Long‐Term Warming in High‐Latitude Carbon‐Limited Soils - Ana Leticia Zevenhuizen; Andreas Richter; Lucia Fuchslueger; Judith Prommer; Ivan A. Janssens; Niel Verbrigghe; Josep Peñuelas; Bjarni D. Sigurdsson; Sara Marañón‐Jiménez (Global Change Biology, 2026)
High‐latitude soils are warming rapidly due to climate change, raising concerns about long‐term impacts on nitrogen (N) and carbon (C) cycling. Here, we investigate how decadal soil warming affects microbial N transformations in subarctic grasslands using natural geothermal gradients with soil temperatures ranging from ambient to +12.3°C. Seasonal measurements of N‐pools and gross N transformation rates—including the production and uptake of amino acids, ammonium, and nitrate—were used to characterize microbial responses across warming intensities and time. Warming enhanced microbial turnover of amino acids by accelerating both gross amino acid production and uptake, while net depolymerization remained unchanged. In contrast, ammonium production remained stable, but its microbial uptake increased significantly with temperature. These decoupled responses suggest a microbial shift toward preferential use of organic N sources under warming, likely driven by reduced soil C availability. This strategy provides a dual source of C and N, enabling microbes to sustain high metabolic activity while limiting additional N losses. Supporting this, total soil N stocks declined early in the warming period—by 0.11 tons of nitrogen per hectare per degree Celsius over 5 years—but remained stable thereafter, indicating a transition toward more conservative microbial N cycling. Together, these findings reveal that long‐term warming restructures microbial N use strategies, favoring tight organic N recycling and mineral N conservation. These physiological adjustments may buffer N losses under future warming and should be integrated into models predicting high‐latitude ecosystem responses to climate change.